Prevalência de halitose em adolescentes e sua importância para a qualidade de vida - Teixeira, Juliana Cunha [UNIFESP] (2019)
Objective: To verify the prevalence of halitosis, quality of life, economic level, VPI (Visible Plaque Index) and DMFT (Dental Caries Index) of adolescents in the Parelheiros district of São Paulo. Methods: This is a quantitative, observational, cross-sectional study composed of a randomized sample conducted in public schools in Parelheiros district. The sample consisted of 238 adolescents aged 15-19 years, high school students from state public schools. The evaluation was performed through a questionnaire with questions about health, OHIP-14 quality of life questionnaire, through a simple clinical examination and also with the BreathAlertTM halitosis sulfide monitor. Values ≥2 were considered positive for halitosis. The study was approved by UNIFESP CEP under Opinion No. 3,098,407. Results: The results showed a prevalence of 3.4% for halitosis in adolescents and a tendency to impact on their quality of life. No relationship was found between halitosis, economic level, VPI and DMFT in the population evaluated. Conclusion: The prevalence of halitosis found among adolescents was low and there was no relationship between halitosis, economic level, VPI and DMFT. Nevertheless, halitosis tends to impact social life.